2009
DOI: 10.1111/j.1747-4477.2009.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of assessing dye penetration along root canal fillings using methylene blue

Abstract: Methylene blue (MB) remains the most frequently used tracer for dye penetration tests of endodontic fillings, despite its chemical reactions with different materials. This study checked whether dye penetration displayed by MB is comparable to Rhodamine B (RB). One hundred and seventy-two root canals were filled with gutta-percha and six sealers. Samples were covered with nail varnish except for the apical area, and immersed in MB or RB solutions under negative pressure. After 24 h, roots were bisected, photogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…This dye has some disadvantages such as dissolution during the demineralization and clearing processes; in addition, it is difficult to observe its maximum penetration point in some cases (49). A number of studies have suggested that Rhodamine B be used instead of methylene blue (50). One study reported that drawing ink exhibited less penetration into the root dentin compared to all the others (24).…”
Section: Resultsmentioning
confidence: 99%
“…This dye has some disadvantages such as dissolution during the demineralization and clearing processes; in addition, it is difficult to observe its maximum penetration point in some cases (49). A number of studies have suggested that Rhodamine B be used instead of methylene blue (50). One study reported that drawing ink exhibited less penetration into the root dentin compared to all the others (24).…”
Section: Resultsmentioning
confidence: 99%
“…, Souza et al . ). Rhodamine B was also shown to affect the properties of MTA and glass–ionomer cements (Camilleri & Pitt Ford ).…”
Section: Discussionmentioning
confidence: 97%
“…There are also limitations associated with individual models, particularly those involving dye leakage evaluation [6973]. Even the most logical model for examining reinfection of root-treated teeth, the microbial leakage model, suffers from severe criticism in that most of the studies published to date lack an appropriate control that takes into account the leakage between the root surface cementum and the sticky wax coating [74,75].…”
Section: The Classics (Traditional Gutta-percha and Sealer)mentioning
confidence: 99%
“…Although the use of methylene blue dye has been criticized in a subsequent study for its futility as a tracer for dye penetration studies due to its chemical reaction with some sealers [73], the endodontic academia at large is skeptical of the clinical implications of currently available in-vitro sealability models, and the absence of evidence associated with studies utilizing these models. As an illustration, Shanahan and Duncan recently published a review paper on root canals obturated by a recently-introduced root filling material that has been introduced into the market as a replacement for gutta-percha [82].…”
Section: The Classics (Traditional Gutta-percha and Sealer)mentioning
confidence: 99%